The Extraction of Essential Oil from Piper Cubeba by Using Solvent Free Microwave Extraction Method - Norma Eralita; Siti Khuzaimah (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2020)
This research aims to study the production of essential oil from Piper Cubeba using the solvent-free microwave extraction (SFME) method. Before extraction, the raw materials are prepared in the form of grains and powders to vary the size of the raw materials. Time variation was carried out at microwave power 180 Watt Analyses were then performed on the resulting essential oil using both physical and chemical tests of density and solubility with 96% alcohol. Analyses of chemical compounds within the essential oil were then performed using the Gas Chromatograph Mass Spectrometry (GC-MS). It was found that the production of essential oil from Piper Cubeba using the SFME method was affected by microwave power, grain size, and treatment duration. Results from physical and chemical analyses revealed that the resulting cubeb oil has 0.86 g/mL density, which means that essential oil produced using the SFME method is lighter compared than those produced using MAHD methods. Results from GC-MS analyses showed eight components detected from the production of essential oil from Piper cubeba using the SFMEmethod; Copaene (39.28%), Cubebene (23.83%), Isoledene (11.66%), Naphthalene (6.65%), Phellandrene (5.81%), Asarone (5.71%), Cadidene (4.90%), and Caryophyllene (2.16%) which contents belong to the sesquiterpene group